Bibliometry, an eficcient to assess the postgraduate scientific activity - Edita Solano López; Sara J. Castellanos Quintero; María Magdalena López Rodríguez del Rey; Juana I. Hernández Fernández (Medisur)
This paper discusses about the importance of bibliometric studies in order to assess the postgraduate scientific activity and proposes indicators to evaluate the scientific production in the postgraduate education in its variant the Master Course and its final product: The Master Thesis, which constitutes the best way to satisfy the ever growing social needs within a context that demands the production and diffusion of knowledge which also requires a constant evaluation.